Остатки китайского белкообразного бурундука (Rodentia, Sciuridae) из верхнемиоценовых отложений Причерноморья Украины - Топачевский, В.А. (Вестник зоологии, 1971)
The new species — Sciurotamias gromovi (the genus Sciurotamias) is described.
This species together with the Hungaria n Miocenic Sciurotamias sciurinus Kretzo i
form the original fossil subgenus Csakvaromys peculiar to Europe. Remains of the new
species originated Ггот the meotic deposits outcropping in the upper reaches of the Berezankian liman valley near vil. Andreevka (not for from Berezanka), the Bcrczankian
district of the Nicolaev region.
Sciurotamias gromovi sp. n. as distinct from the Hungaria n S. sciurinus is less in size,
mental foramen in it is displaced upwards, its margin s are not raised above the mandible
diastema, the low masseteric part reaches the level of the P4 middle.
The finding of Sciurotamias gromovi and S. sciurinus in the Miocenic deposits of
Europe is one more evidence for the similarity of the European Neogene fauna s with the
modern fauna of South-Eastern Asia.